Metode Pembelajaran Bahasa Arab - Nur Rokhhmatulloh (Universitas Yudharta Pasuruan, 2017)
Learning plays an important role in maintaining the lives of a group of human beings (nations) in the midst of increasingly fierce competition among other nations that advance ahead of learning. From here learning is a process so that humans can make life more alive that has a better direction and can be useful for other humans, so that human life can survive as humans who are educated, moral and civilized. But many are found in the learning process that occurs without regard to the psychological and sociological conditions of students which will actually have a negative impact and will result in mental and soul disturbed and damage the social order. This shows that